CSV-SDGs Synergies And Their Challenges: A Literature Review: Sinergi CSV-SDGs dan Tantangannya: Sebuah Telaah Literatur - Fala, Dwi Yana Amalia Sari; Purwanti, Lilik (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Cirebon, 2024)
This paper explores the synergies and challenges of integrating Creating Shared Value (CSV) with Sustainable Development Goals (SDGs), two important concepts in global sustainability discourse. CSV links economic value creation to increased social and environmental value, while the SDGs provide a framework for addressing pressing global development challenges. Although the two have similar goals, the synergy between them has not been fully tapped. Through an in-depth literature review, the paper identifies key barriers to CSV and SDGs integration, including lack of strategic understanding and commitment, barriers to innovation, and measurement difficulties. The paper offers practical recommendations for addressing these challenges, including improved strategic coordination, investment in innovation, and adaptation to organizational culture. Implications for business practices and public policy were also discussed, highlighting the importance of cross-sector collaboration to achieve SDGs goals through CSV practices. The results show that by addressing these integration challenges, companies can become agents of positive change, creating sustainable economic value while delivering significant social and environmental benefits.